IMPROVING THE ABILITY TO RECOGNIZE NUMBERS THROUGH THE NUMBER SPINNING WHEEL MEDIA IN CHILDREN AGED 4-5 YEARS - Vani, Annisa Mutiara; Dema Yulianto; Widi Wulansari (Mathematics Research and Education Journal, 2025)
This study is motivated by the results of observations of researchers in group A children at Dharma Wanita Sitimerto Kindergarten, there are still many children who are lacking in their ability to recognize numbers 1-10. This can be seen from the learning methods and learning media that are monotonous and do not attract children's attention when learning so that children are less focused on learning delivered by the teacher. This study uses classroom action research (PTK) with research subjects of 4-5 years old children totaling 19 children at Dharma Wanita Sitimerto Kindergarten, Kediri Regency. This study used numerical rotating wheel media which was implemented in two cycles. Data collection methods using observation sheets and documentation. The child observation sheet has 4 indicators that are used to determine the level of success and evaluation material in each cycle. This study began by making observations in the pre-cycle with the results of completeness of 57.89% then an increase in cycle I of 63.16% after being given action in the form of learning by using numerical rotating wheel media. This also happened in cycle II which experienced an increase in percentage to 84.21% after being given action.